Regulation of On-Tree Vitamin E Biosynthesis in Olive Fruit during Successive Growing Years: The Impact of Fruit Development and Environmental Cues - Georgiadou, Egli C.; Goulas, Vlasios; Ntourou, Thessaloniki; Manganaris, George A.; Kalaitzis, Panagiotis; Fotopoulos, Vasileios (Frontiers in Plant Science, 2016)
The term vitamin E refers to a group of eight lipophilic compounds known as tocochromanols. The tocochromanols are divided into two groups, that is, tocopherols and tocotrienols, with four forms each, namely α-, β-, γ-, and δ-. In order to explore the temporal biosynthesis of tocochromanols in olive (Olea europaea cv. ‘Koroneiki’) fruit during on-tree development and ripening over successive growing years, a combined array of analytical, molecular, bioinformatic, immunoblotting and antioxidant techniques were employed. Fruits were harvested at eight successive developmental stages (10-30 weeks after flowering (WAF)), over three consecutive years. Intriguingly, climatic conditions affected relative transcription levels of vitamin E biosynthetic enzymes; a general suppression to induction pattern (excluding VTE5) was monitored moving from the 1st to the 3rd growing year, probably correlated to decreasing rainfall levels and higher temperature, particularly at the fruit ripening stage. A gradual diminution of VTE5 protein content was detected during the fruit development of each year, with a marked decrease occurring after 16 WAF. Alpha-tocopherol was the most abundant metabolite with an average percentage of 96.82 ± 0.23%, 91.13 ± 0.95% and 88.53 ± 0.96% (during the 1st, 2nd and 3rd year, respectively) of total vitamin E content in 10–30 WAF. The concentrations of α-tocopherol revealed a generally declining pattern, both during the on-tree ripening of the olive fruit and across the three years, accompanied by a parallel decline of the total antioxidant activity of the drupe. Contrarily, all other tocochromanols demonstrated an inverse pattern with lowest levels being recorded during the 1st year. It is likely that, in a defense attempt against water deficit conditions and increased air temperature, transcription of genes involved in vitamin E biosynthesis (excluding VTE5) is up-regulated in olive fruit, probably leading to the blocking/deactivating of the pathway through a negative feedback regulatory mechanism.